Genetic variants in FBN-1 and risk for thoracic aortic aneurysm and dissection. - Olga A Iakoubova; Carmen H Tong; Charles M Rowland; May M Luke; Veronica E Garcia; Joseph J Catanese; Remo M Moomiaie; Peter Sotonyi; Gyorgy Ascady; Demitrios Nikas; Panagiotis Dedelias; Maryann Tranquilli; et al. (PLoS ONE, 2014)
A recent genome wide association study (GWAS) by LeMaire et al. found that two single nucleotide polymorphisms (SNPs), rs2118181 and rs10519177 in the FBN-1 gene (encoding Fibrillin-1), were associated with thoracic aortic dissection (TAD), non-dissecting thoracic aortic aneurysm (TAA), and thoracic aortic aneurysm or dissection (TAAD); the largest effect was observed for the association of rs2118181 with TAD. We investigated whether rs2118181 and rs10519177 were associated with TAD, TAA, and TAAD in the Yale study.The genotypes of rs2118181 and rs10519177 were determined for participants in the Yale study: 637 TAAD cases (140 TAD, 497 TAA) and 275 controls from the United States, Hungary, and Greece. The association of the genotypes with TAD, TAA and TAAD were assessed using logistic regression models adjusted for sex, age, study center and hypertension.In the Yale study, rs2118181 was associated with TAD: compared with non-carriers, carriers of the risk allele had an unadjusted odds ratio for TAD of 1.80 (95% CI 1.15-2.80) and they had odds ratio for TAD of 1.87 (95% CI 1.09-3.20) after adjusting for sex, age, study center and hypertension. We did not find significant differences in aortic size, a potential confounder for TAD, between rs2118181 risk variant carriers and non-carriers: mean aortic size was 5.56 (95% CI: 5.37-5.73) for risk variant carriers (CC+CT) and was 5.48 (95% CI: 5.36-5.61) for noncarriers (TT) (p = 0.56). rs2118181 was not associated with TAA or TAAD. rs10519177 was not associated with TAD, TAA, or TAAD in the Yale study. Thus, the Yale study provided further support for the association of the FBN-1 rs2118181SNP with TAD.